Effects of Traditional Medicine on Fat-Tailed Sheep's Performance - Soebarinoto (Soebarinoto); T. Y. Astuti; Hermanto (Hermanto); Marjuki (Marjuki) (Buletin Peternakan, 1995)
Abstract dalam bentuk hard copy